Instrumentos psicológicos y la teoría de la actividad instrumentada: fundamento teórico para el estudio del papel de los recursos tecnológicos en los procesos educativos - Ballestero Alfaro, Esteban (2008)
In this writing, you will be informed about the most important ideas that characterize the psychological instruments in the Vygostkian theory, as well as the Instrumental Activity theory written by Verillon & Rabardel. In this sense, this article presents an analysis about common elements and differences between these theories, besides their relevance and pertinence when one desires to determine the impact of technology within the teaching and learning processes. In addition, it is intended to promote a critical attitude toward the reader that wants to use (or that is already using) some type of technological resource to teach.